2021
DOI: 10.1016/j.clinthera.2021.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns Among Patients With Mantle Cell Lymphoma and Comparison of Healthcare Resource Utilization and Costs Among Relapsed/Refractory Patients Treated With Ibrutinib or Chemoimmunotherapy: A Real-world Retrospective Study

Abstract: Purpose: This study assessed treatment patterns in patients with mantle cell lymphoma (MCL) and compared health care resource utilization (HRU) and costs of ibrutinib with or without rituximab (I ± R) versus chemoimmunotherapy (CIT) in patients with relapsed/refractory MCL.Methods: For this retrospective cohort study, adults with MCL observed between May 13, 2013, and June 30, 2019, were identified using Optum's de-identified Clinformatics Data Mart Database. Treatment patterns were described among patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…This observation may be explained by off-label use or misclassification of LOT caused by limitations of the database that cannot track beyond a single hospital. The proportion of patients who underwent ASCT was 9.2%, which was similar to previous findings which utilized the MDV database in Japan (8.5%) and the Optum Clinformatics Data Mart database in the USA (6.9–7.3%) [ 26 , 35 ]. However, other studies from the UK and Norway reported higher rates of ASCT of 24% [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 86%
“…This observation may be explained by off-label use or misclassification of LOT caused by limitations of the database that cannot track beyond a single hospital. The proportion of patients who underwent ASCT was 9.2%, which was similar to previous findings which utilized the MDV database in Japan (8.5%) and the Optum Clinformatics Data Mart database in the USA (6.9–7.3%) [ 26 , 35 ]. However, other studies from the UK and Norway reported higher rates of ASCT of 24% [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 86%